2021
DOI: 10.1155/2021/4560580
|View full text |Cite
|
Sign up to set email alerts
|

The Evolutionary Game Analysis of Public Opinion Supervision of Engineering Quality in the Network Citizen Journalism Environment

Abstract: With the rapid development of mobile networks and citizen journalism, public opinion supervision has become an essential social supervision on engineering quality. They consider the dynamic characteristics of the spread process of public opinion and the game process of social supervision on engineering quality. The tripartite evolutionary game model of the government, contractors, and the public was constructed by coupling the Susceptible-Exposed-Infected-Removed (SEIR) model of public opinion spread and the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 12 publications
1
7
0
Order By: Relevance
“…The political institutions inspected 65.98% of the schools for faith and knowledge education [ 21 ] (see Figure 10 ).…”
Section: Current Status and Issues Of College Students' Ideological A...mentioning
confidence: 99%
See 1 more Smart Citation
“…The political institutions inspected 65.98% of the schools for faith and knowledge education [ 21 ] (see Figure 10 ).…”
Section: Current Status and Issues Of College Students' Ideological A...mentioning
confidence: 99%
“…From the perspective of the importance attached by vocational schools to the management of ideological and political education, 97.94% thought that the school attached great importance to, attached importance to, or generally attached importance to it, and only 2.06% thought that the school did not attach much importance to the management of ideological and political education, and chose the person who "did not attach importance to" as 0, which has a certain relationship with the characteristics of poor organizational discipline and lack of consciousness of vocational school students (see Figure 9). e political institutions inspected 65.98% of the schools for faith and knowledge education [21] (see Figure 10).…”
Section: Ideological and Political Education Management Organization ...mentioning
confidence: 99%
“…He et al (2021) and Wen et al (2021) studied the quality supervision of online shopping from the perspective of government regulation by using evolutionary game theory. Yang et al (2021) built an evolutionary game model of the government, contractors, and the public to study the problem of project quality supervision. Sun et al (2022) constructed an evolutionary game model based on prospect theory to study carbon emission regulation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Miller, R. J et al argued that formal legal exclusionary behaviors would increase the emergence of criminal behaviors to a certain extent, and emphasized the monitoring rights and responsibilities possessed by political citizens have nothing to do with race, and that political citizens should fully understand their own identities [11]. Yang, Y et al argued that public opinion monitoring, as a kind of social monitoring, has a restraining effect on social behaviors, and analyzed the dynamic characteristics of public opinion dissemination and the influence law on the three parties by establishing a three-party evolutionary game model among the government, contractors and the public three-party evolutionary game model to analyze the dynamic characteristics of public opinion dissemination and the law of influence on the three parties [12]. Meixi, Z addressed the imbalance phenomenon of social accountability, explored the influencing factors to promote the innovation of social accountability by investigating the data of public supervision of local governments, and concluded that the opinions of localities and citizens need to be in line with each other [13].…”
Section: Introductionmentioning
confidence: 99%